2005
DOI: 10.1097/01.ijg.0000169391.94555.c1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Encapsulated Cysts Following Ahmed Glaucoma Valve Insertion

Abstract: Encapsulated cysts associated with elevated intraocular pressure were commonly seen after Ahmed glaucoma valve implant insertion. Failing medical therapy, surgical excision of the cyst is effective in lowering intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 25 publications
1
50
2
1
Order By: Relevance
“…[48][49][50] Postoperative complications after AVI include hypotony (IOPp5 mm Hg) (11-42%), shallow anterior chamber (15 B26%), tube malposition (5B26%), tubecorneal touch (3B8%), tube occlusion (14%), tube exposure (6B12%), and other rare complications such as tenon encapsulated cyst (1B7%), postoperative cataract (0B2%), strabismus (0B3%), retinal or choroidal detachment (1B18%), endophthalmitis (1B5%), wound leak (3%), plate migration (2%), inflammation, hyphema, delayed retrobulbar haemorrhage. [28][29][30]33,39,51,52 In our study, overall rates of complications was lower than previously reported. Shallow anterior chamber (8.8%) was most commonly encountered, but found in a lower rate compared to other studies.…”
Section: Discussioncontrasting
confidence: 54%
“…[48][49][50] Postoperative complications after AVI include hypotony (IOPp5 mm Hg) (11-42%), shallow anterior chamber (15 B26%), tube malposition (5B26%), tubecorneal touch (3B8%), tube occlusion (14%), tube exposure (6B12%), and other rare complications such as tenon encapsulated cyst (1B7%), postoperative cataract (0B2%), strabismus (0B3%), retinal or choroidal detachment (1B18%), endophthalmitis (1B5%), wound leak (3%), plate migration (2%), inflammation, hyphema, delayed retrobulbar haemorrhage. [28][29][30]33,39,51,52 In our study, overall rates of complications was lower than previously reported. Shallow anterior chamber (8.8%) was most commonly encountered, but found in a lower rate compared to other studies.…”
Section: Discussioncontrasting
confidence: 54%
“…4 The encapsulated bleb is impervious to the aqueous humor, which results in intraocular pressure elevation. 10,11 The incidence of bleb encapsulation is much higher with the AGV than the other glaucoma drainage implants and has been estimated to be between 40% and 80%, 12 which might be attributed to certain factors of the aqueous humor that stimulate a fibrotic response. Tsai et al 13 have suggested that immediate aqueous filtration with inflammatory factors may stimulate the fibrotic response in the subconjunctival space when the Ahmed implant is used, and delayed flow with a ligated, nonvalved implant may elicit a less fibrous reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, glaucoma implants including AGVs stimulate a foreign body fibrotic response that encapsulates the glaucoma implant body and increases aqueous outflow resistance through the capsule. This can lead to elevated intraocular pressure (IOP) requiring further surgical intervention [2,3]. …”
Section: Introductionmentioning
confidence: 99%